Measuring team learning behaviours through observing verbal team interaction. Issue 7 (14th September 2015) - Raes, Elisabeth; Boon, Anne; Kyndt, Eva; Dochy, Filip
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to explore, as an answer to the observed lack of knowledge about actual team learning behaviours, the characteristics of the actual observed basic team learning behaviours and facilitating team learning behaviours more in-depth of three project teams. Over time, team learning in an organisational context has been investigated more and more. In these studies, there is a dominant focus on team members' perception of team learning behaviours. Design/methodology/approach – A coding schema is created to observe actual team learning behaviours in interaction between team members in two steps: verbal contributions by individual team members are coded to identify the type of sharing behaviour and, when applicable, these individual verbal behaviours are build up to basic and facilitating team learning behaviours. Based on these observations, an analysis of team learning behaviours is conducted to identify the specific characteristics of these behaviours. Findings – An important conclusion of this study is the lack of clarity about the line of demarcation between individual contributions and learning behaviours and team learning behaviours. Additionally, it is clear that the conceptualisations of team learning behaviour in previous research neglect to a large extend the nuances and depth of team learning behaviours. Originality/value – Due to the innovative approach to study team learning behaviours, this study is of great value to the research field of teamwork for two reasons: the creation of a coding schema to analyse team learning behaviours and the findings that resulted from this approach.